RELATION BETWEEN PARAMETERS OF STRENGTH AND RESILIENCE OF THE ROCKS DEPENDING ON THEIR LEVEL OF HUMIDITY (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The paper presents regular changes in strength and resilience of rocks and their mutual dependence in the entire range of humidity. It was revealed that in the range of maximum hygroscopic humidity up to W=20% the strength and resilience modules of rocks are abruptly reduced, and then until the humidity 70% the stabilization of values of mentioned parameters is registered. Subsequently, until it approaches 100%, the parameters start to increase to values corresponding to absolute dry condition of these rocks.
Keywords: use of the stamp; humidity; strength; resilience; longitudinal and transverse waves